Specific detection of Treponema pallidum in clinical samples: validation of a qPCR assay combining two genomic targets. (22nd April 2022) - Salle, Romain; Mayslich, Constance; Grange, Philippe Alain; Leducq, Valentin; Ollagnier, Guillaume; Heller, Ugo; Saule, Julie; Martinet, Pervenche; Robert, Jean-Luc; Benhaddou, Nadjet; Fouere, Sebastien; Dupin, Nicolas
Abstract : Objectives: We evaluated a real-time quantitative PCR (qPCR) for detection of the Treponema pallidum (TP) genome in clinical samples through simultaneous detection of two genomic targets. Methods: We performed qPCR with TaqMan technology using two TP genes, polA and tpp47, as targets, with an internal positive control. The qPCR assay was compared with syphilis diagnosis based on a combination of clinical examination, serological results and inhouse nested PCR (nPCR). Samples were analysed at the National Reference Center for STIs at Cochin Hospital in Paris. Results: In total, from October 2010 to December 2016, 320 documented clinical samples (mucosal and cutaneous swabs) were collected from patients with or without syphilis attending STI centres in France. The qPCR had an overall sensitivity of 89% (95% CI 85.1% to 92.1%), a specificity of 100%, a positive predictive value of 100% and a negative predictive value of 88% (95% CI 84.3% to 91.5%). The agreement between qPCR and nPCR results was 94% ( κ =0.88, 95% CI 0.83 to 0.93). Calibration of the qPCR assay, by cloning both the polA and tpp47 genes, defined the detection threshold as 1 copy/µL of DNA elution. Conclusions: We validated a new qPCR for detecting the TP genome in clinical samples with excellent sensitivity and specificity. The cloning of polA and tpp47 genes for calibration would be interesting in the evaluation of bacterial loads in samples.